HUBUNGAN LAMA WAKTU PASCA KEMORADIASI DENGAN DERAJAT DISFAGIA OROFARINGEAL PADA KARSINOMA NASOFARING - Kusuma, Lirans Tia; Antono, Dwi; Muyassaroh, Muyassaroh (RSUP Dr. Kariadi, 2021)
Abstract Background : Dysphagia can occur as a side effect in patients with nasopharyngeal carcinoma (NPC) receiving chemoradiation therapy. The reported incidence rate up to 83%. The degree of oropharyngeal dysphagia accosiated with the long time of post-chemoradiation in NPC is not yet clearly known. Objective : To analysis the degree of oropharyngeal dysphagia accosiated with the long time of post-chemoradiation in NPC. Method : Analysis observational research with cross sectional design. The subjects were patients with post-chemoradiation NPC at RSUP Dr. Kariadi Semarang who met the inclusion criteria. Determination of dysphagia status and degree of dysphagia by Gugging Swallowing Screen (GUSS). The complete details of the subjects were obtained from history and medical records. Chi-Squared is used for the statistical test. Outcome : Fifty five (100%) subjects had dysphagia, 48 (87.3%) subjects had mild degrees of dysphagia, no subjects with moderate degree of dysphagia were found, and 7 (12.7%) subjects had severe dysphagia. Long time of post-chemoradiation (p = 0.451), type of chemotherapy (p = 0.267), and therapeutic modality (p = 0.402) were not related to the degree of oropharyngeal dysphagia in NPC. Conclusion : The majority of subjects had mild degree dysphagia. Long time of post-chemoradiation, type of chemotherapy, and modality of therapy are not related to the degree of oropharyngeal dysphagia in NPC. Keywords: NPC, chemoradiation, degree of dysphagia, GUSS.